Familial Focal Segmental Glomerulosclerosis With Late-Onset Presentation and R229Q/R291W Podocin Mutations - Riguetti, Michelle T. P.; Varela, Patrícia; Fernandes, Danilo E.; Polito, M. Goretti; Casimiro, Fernanda M.; Pesquero, João B.; Mastroianni-Kirsztajn, Gianna (Frontiers in Genetics, 2020)
Introduction: Pathogenic variants in different genes have been described as involved in the development of familial focal segmental glomerulosesclerosis (FSGS). A more precise genotype-phenotype correlation would be helpful to better characterize the clinical and laboratorial manifestations of this disease, as well as response to treatment. We analyzed podocin (NPHS2) gene variants in 50 members of four generations of a family with late onset presentation of glomerular disease. Results and discussion: The NPHS2 gene variants R229Q and/or R291W were detected in several individuals and the phenotype of FSGS with progressive loss of renal function was observed in all the family members carrying both mutations simultaneously. Patients manifested ongoing proteinuria over the years and progressive loss of renal function, which in three women culminated in renal replacement therapy by the 4th decade of life. In two affected patients with nephrotic syndrome, remission was not reached by the use of corticosteroids and other immunosuppressive drugs. The R229Q variant was pathogenic only when trans-associated to specific mutations, as the R291W variant in this family. Conclusion: Coexistence of the two NPHS2 variants R229Q and R291W in compound heterozygosis was determinant of the FSGS phenotype. The presence of these variants alone in heterozygosis did not cause significant proteinuria.